Arteriovenous malformation of the mandible and parotid gland - Shailaja, S R (The British Institute of Radiology., 2012)
Arteriovenous malformations (AVMs) of the jaws are relatively rare, with fewer than 200 cases reported in the literature. Their real importance lies in their potential to result in exsanguination, which usually follows an unrelated treatment, such as tooth extraction, surgical intervention, puncture wound or blunt injury in involved areas, with the dentist unaware of the existence of the AVM. The present case illustrates an AVM in an 18-year-old female with swelling on the right side of the face. This case report is unique because although there was no history of bleeding episodes, thorough examination and investigation diagnosed it as high-flow vascular malformation. We ascertain the importance of dentists' awareness of the fatal outcome of these lesions and emphasize that, prior to performing any procedure, necessary investigations should always be done.